Towards a Refined Definition of “tidal Influence” for the Coastal Wetland Sciences - Ken W. Krauss; Laura S. Brophy; Judith Z. Drexler; Jeffrey A. Kelleway; Janine B. Adams; Havalend E. Steinmuller; Gregory B. Noe; Michael J. Osland; Jamie A. Duberstein; Kurt P. Kowalski; Amanda L. McCutcheon; Kaileʻa M. Annandale; et al. (Wetlands, 2026)

DEFINING THE RISKS OF CONTAMINANT EXPOSURE TO PELAGIC SPECIES IN A SHIPPING CHANNEL - Cristina G.B. La; Kara E.Huff Hartz; Nick M. Hettel; Giovanni S. Molinari; Emerson Feddor; Shawn Acuña; Jacob Stagg; Amelie Segarra; Michael J. Lydy (Environmental Pollution, 2026)

Loss and Transformation of Coastal Wetlands due to Global Change in the Conterminous United States: Past, Present, and Future - Michael J. Osland; Bogdan Chivoiu; Kevin J. Buffington; Kristin B. Byrd; Joel A. Carr; Judith Z. Drexler; Nicholas M. Enwright; Neil K. Ganju; James. B. Grace; Eric E. Grossman; Glenn R. Guntenspergen; Kurt P. Kowalski; et al. (Wetlands, 2026)
Coastal wetlands are being transformed by global change, impacting the ecological and societal benefits provided by these ecosystems. Synthesizing knowledge of historical and expected future transformations in coastal wetlands can help inform forward-looking planning and stewardship efforts. Here, we review anticipated future ecological transformations in coastal wetlands of the conterminous United States and contrast them with past transformations. We examine trends at the national scale but focus in detail on the following six wetland-rich regions: (1) Everglades, (2) Mississippi River delta, (3) Chesapeake Bay, (4) San Francisco Estuary, (5) Puget Sound, and (6) Great Lakes. This review is among the first to integrate and compare coastal wetland transformations in the Great Lakes with their oceanic counterparts. Between 1850 and 1970, wetland losses across the nation were high because coastal wetlands were viewed as flooded wastelands needing to be drained, filled, or excavated to make room for other land uses. Over the last 50 years, growing public and scientific appreciation of the ecological and societal benefits provided by coastal wetlands has fostered tremendous gains in wetland restoration and legal protection. Looking to the future, climate change and accelerated sea-level rise have become critical threats to coastal wetlands and are emerging as major drivers of ecological loss and transformation. This review synthesizes regional knowledge regarding past, present, and future changes to help coastal scientists, environmental managers, and the public better anticipate and prepare for future coastal wetland transformations due to climate change, accelerated sea-level rise, land-use change, and other aspects of global change.

Thermochemical valorization of industrial hemp residues: Advances in hydrothermal conversion for biofuels and chemicals - Lateef A. Jolaoso; Susan M. Stagg-Williams; Jude A. Okolie (Biomass and Bioenergy, 2026)

Hydrothermal liquefaction of sludge: Impact of enhanced biological phosphorus removal and lime addition on product characteristics - João V. Poli; Daniel V. Tabaka; Maria R. Garcia; Belinda S.M. Sturm; Susan M. Stagg-Williams (Journal of Environmental Chemical Engineering, 2025)

The role of central cavity arginine residues in UCP1 proton leak - Hannah R. Staggs; Mehmethan Aris; Camila A. Cotrim; Danielle M. Copeman; Paul G. Crichton (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

Characterising the ligand interactions and properties of purified UCP1 isoforms - Mehmethan Aris; Riccardo Cavalieri; Danielle M. Copeman; Camila A. Cotrim; Hannah R. Staggs; Paul G. Crichton (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

Integrating Remote Sensing with Ground-based Observations to Quantify the Effects of an Extreme Freeze Event on Black Mangroves (Avicennia germinans) at the Landscape Scale - Melinda Martinez; Michael J. Osland; James B. Grace; Nicholas M. Enwright; Camille L. Stagg; Simen Kaalstad; Gordon H. Anderson; Anna R. Armitage; Just Cebrian; Karen L. Cummins; Richard H. Day; Donna J. Devlin; et al. (Ecosystems, 2024)

Practical Guide to Measuring Wetland Carbon Pools and Fluxes - Sheel Bansal; Irena F. Creed; Brian A. Tangen; Scott D. Bridgham; Ankur R. Desai; Ken W. Krauss; Scott C. Neubauer; Gregory B. Noe; Donald O. Rosenberry; Carl Trettin; Kimberly P. Wickland; Scott T. Allen; et al. (Wetlands, 2023)
Wetlands cover a small portion of the world, but have disproportionate influence on global carbon (C) sequestration, carbon dioxide and methane emissions, and aquatic C fluxes. However, the underlying biogeochemical processes that affect wetland C pools and fluxes are complex and dynamic, making measurements of wetland C challenging. Over decades of research, many observational, experimental, and analytical approaches have been developed to understand and quantify pools and fluxes of wetland C. Sampling approaches range in their representation of wetland C from short to long timeframes and local to landscape spatial scales. This review summarizes common and cutting-edge methodological approaches for quantifying wetland C pools and fluxes. We first define each of the major C pools and fluxes and provide rationale for their importance to wetland C dynamics. For each approach, we clarify what component of wetland C is measured and its spatial and temporal representativeness and constraints. We describe practical considerations for each approach, such as where and when an approach is typically used, who can conduct the measurements (expertise, training requirements), and how approaches are conducted, including considerations on equipment complexity and costs. Finally, we review key covariates and ancillary measurements that enhance the interpretation of findings and facilitate model development. The protocols that we describe to measure soil, water, vegetation, and gases are also relevant for related disciplines such as ecology. Improved quality and consistency of data collection and reporting across studies will help reduce global uncertainties and develop management strategies to use wetlands as nature-based climate solutions.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Correction to: “Relationships Between Salinity and Short-Term Soil Carbon Accumulation Rates from Marsh Types Across a Landscape in the Mississippi River Delta” - Melissa M. Baustian; Camille L. Stagg; Carey L. Perry; Leland C. Moss; Tim J. B. Carruthers; Mead Allison (Wetlands, 2020)

First isolation of Flavobacterium psychrophilum associated with reports of moribund wild European eel ( Anguilla anguilla ) in Scotland - Sílvia M. C. Soares; Amanda Walker; Svenja A. Elwenn; Sion Bayliss; Alison Garden; Hannah E. B. Stagg; Eann S. Munro (Journal of Fish Diseases, 2019)
In late April 2015, the River Dee Trust informed Marine Scotland Science, Fish Health Inspectorate (FHI), that there had been observations of dead and moribund European eels on the River Dee. Later in May, the Spey Fishery Board also reported a number of moribund European eels in a rotary screw smolt trap on the River Spey. In total, 10 cases involving moribund eels were investigated in 2015 and one case in 2016. In addition, a health screen was conducted to investigate the potential presence of Flavobacterium psychrophilum in healthy eels and Atlantic salmon from the River Dee in 2015. Externally, the diseased eels demonstrated white patches in different locations of the body. In all cases, F. psychrophilum was detected by bacterial isolation and/or molecular methods. Three isolates were further characterized by whole‐genome sequencing (WGS) as belonging to sequence type 15 (ST15). Histological examination of diseased European eels revealed lesions at the level of the integument. The pathogen screen for F. psychrophilum in wild healthy fish tested negative by PCR. Further investigation is required to understand the pathogenicity of this bacterium on the health of eels and the potential impact on the wild salmonid population.

Targeted inhibition of histone deacetylase leads to suppression of Ewing sarcoma tumor growth through an unappreciated EWS-FLI1/HDAC3/HSP90 signaling axis - Yan Ma; Michael Baltezor; Lian Rajewski; Jennifer Crow; Glenson Samuel; Vincent S. Staggs; Katherine M. Chastain; Jeffrey A. Toretsky; Scott J. Weir; Andrew K. Godwin (Journal of Molecular Medicine, 2019)

Climate and plant controls on soil organic matter in coastal wetlands - Michael J. Osland; Christopher A. Gabler; James B. Grace; Richard H. Day; Meagan L. McCoy; Jennie L. McLeod; Andrew S. From; Nicholas M. Enwright; Laura C. Feher; Camille L. Stagg; Stephen B. Hartley (Global Change Biology, 2018)
Coastal wetlands are among the most productive and carbon‐rich ecosystems on Earth. Long‐term carbon storage in coastal wetlands occurs primarily belowground as soil organic matter (SOM). In addition to serving as a carbon sink, SOM influences wetland ecosystem structure, function, and stability. To anticipate and mitigate the effects of climate change, there is a need to advance understanding of environmental controls on wetland SOM. Here, we investigated the influence of four soil formation factors: climate, biota, parent materials, and topography. Along the northern Gulf of Mexico, we collected wetland plant and soil data across elevation and zonation gradients within 10 estuaries that span broad temperature and precipitation gradients. Our results highlight the importance of climate–plant controls and indicate that the influence of elevation is scale and location dependent. Coastal wetland plants are sensitive to climate change; small changes in temperature or precipitation can transform coastal wetland plant communities. Across the region, SOM was greatest in mangrove forests and in salt marshes dominated by graminoid plants. SOM was lower in salt flats that lacked vascular plants and in salt marshes dominated by succulent plants. We quantified strong relationships between precipitation, salinity, plant productivity, and SOM. Low precipitation leads to high salinity, which limits plant productivity and appears to constrain SOM accumulation. Our analyses use data from the Gulf of Mexico, but our results can be related to coastal wetlands across the globe and provide a foundation for predicting the ecological effects of future reductions in precipitation and freshwater availability. Coastal wetlands provide many ecosystem services that are SOM dependent and highly vulnerable to climate change. Collectively, our results indicate that future changes in SOM and plant productivity, regulated by cascading effects of precipitation on freshwater availability and salinity, could impact wetland stability and affect the supply of some wetland ecosystem services.

Relationships Between Salinity and Short-Term Soil Carbon Accumulation Rates from Marsh Types Across a Landscape in the Mississippi River Delta - Melissa M. Baustian; Camille L. Stagg; Carey L. Perry; Leland C. Moss; Tim J. B. Carruthers; Mead Allison (Wetlands, 2017)

Processes Contributing to Resilience of Coastal Wetlands to Sea-Level Rise - Camille L. Stagg; Ken W. Krauss; Donald R. Cahoon; Nicole Cormier; William H. Conner; Christopher M. Swarzenski (Ecosystems, 2016)

Beyond just sea‐level rise: considering macroclimatic drivers within coastal wetland vulnerability assessments to climate change - Michael J. Osland; Nicholas M. Enwright; Richard H. Day; Christopher A. Gabler; Camille L. Stagg; James B. Grace (Global Change Biology, 2016)
Due to their position at the land‐sea interface, coastal wetlands are vulnerable to many aspects of climate change. However, climate change vulnerability assessments for coastal wetlands generally focus solely on sea‐level rise without considering the effects of other facets of climate change. Across the globe and in all ecosystems, macroclimatic drivers (e.g., temperature and rainfall regimes) greatly influence ecosystem structure and function. Macroclimatic drivers have been the focus of climate change‐related threat evaluations for terrestrial ecosystems, but largely ignored for coastal wetlands. In some coastal wetlands, changing macroclimatic conditions are expected to result in foundation plant species replacement, which would affect the supply of certain ecosystem goods and services and could affect ecosystem resilience. As examples, we highlight several ecological transition zones where small changes in macroclimatic conditions would result in comparatively large changes in coastal wetland ecosystem structure and function. Our intent in this communication is not to minimize the importance of sea‐level rise. Rather, our overarching aim is to illustrate the need to also consider macroclimatic drivers within vulnerability assessments for coastal wetlands.

A survey of wild marine fish identifies a potential origin of an outbreak of viral haemorrhagic septicaemia in wrasse, L abridae, used as cleaner fish on marine A tlantic salmon, S almo salar L ., farms - I S Wallace; K Donald; L A Munro; W Murray; C C Pert; H Stagg; M Hall; N Bain (Journal of Fish Diseases, 2015)
Viral haemorrhagic septicaemia virus ( VHSV ) was isolated from five species of wrasse ( L abridae) used as biological controls for parasitic sea lice predominantly, Lepeophtheirus salmonis ( K røyer, 1837), on marine A tlantic salmon, S almo salar L ., farms in S hetland. As part of the epidemiological investigation, 1400 wild marine fish were caught and screened in pools of 10 for VHSV using virus isolation. Eleven pools (8%) were confirmed VHSV positive from: grey gurnard, E utrigla gurnardus L .; A tlantic herring, C lupea harengus L .; N orway pout, T risopterus esmarkii ( N ilsson); plaice, P leuronectes platessa L .; sprat, S prattus sprattus L . and whiting, M erlangius merlangus L . The isolation of VHSV from grey gurnard is the first documented report in this species. Nucleic acid sequencing of the partial nucleocapsid ( N ) and glycoprotein ( G ) genes was carried out for viral characterization. Sequence analysis confirmed that all wild isolates were genotype III the same as the wrasse and there was a close genetic similarity between the isolates from wild fish and wrasse on the farms. Infection from these local wild marine fish is the most likely source of VHSV isolated from wrasse on the fish farms.

Ecosystem Development After Mangrove Wetland Creation: Plant–Soil Change Across a 20-Year Chronosequence - Michael J. Osland; Amanda C. Spivak; Janet A. Nestlerode; Jeannine M. Lessmann; Alejandro E. Almario; Paul T. Heitmuller; Marc J. Russell; Ken W. Krauss; Federico Alvarez; Darrin D. Dantin; James E. Harvey; Andrew S. From; et al. (Ecosystems, 2012)

Architecture of volcanic rifted margins: new insights from the Exmouth – Gascoyne margin, Western Australia - N. G. Direen; H. M. J. Stagg; P. A. Symonds; J. B. Colwell (Australian Journal of Earth Sciences, 2008)

Walking performance and its recovery in chronic stroke in relation to extent of lesion overlap with the descending motor tract - H. Dawes; C. Enzinger; H. Johansen-Berg; M. Bogdanovic; C. Guy; J. Collett; H. Izadi; C. Stagg; D. Wade; P. M. Matthews (Experimental Brain Research, 2008)

Geology of the Continental Margin of Enderby and Mac. Robertson Lands, East Antarctica: Insights from a Regional Data Set - H. M. J. Stagg; J. B. Colwel; N. G. Direen; P. E. O’Brien; G. Bernardel; I. Borissova; B. J. Brown; T. Ishirara (Marine Geophysical Research, 2004)

The physiological response of the turbot to multiple net confinements - Colin P. Waring; Michael G. Poxton; Ronald M. Stagg (Aquaculture International, 1997)

The effects of In Vivo exposure to cadmium, copper and zinc on the activities of gill ATPases in the Norway lobster, Nephrops norvegicus - M. Canli; R. M. Stagg (Archives of Environmental Contamination and Toxicology, 1996)